Myopia and its associated factors among pregnant women at health institutions in Gondar District, Northwest Ethiopia: A multi-center cross-sectional study - Diress, Mengistie; Getnet, Mihret; Akalu, Yonas; Dagnew, Baye; Belsti, Yitayeh; Gela, Yibeltal Yismaw; Chilot, Dagmawi; Belay, Daniel Gashaneh; Bitew, Desalegn Anmut; Terefe, Bewuketu; Getahun, Amare Belete (Frontiers in Global Women's Health, 2023)
Background Myopia is the most common form of uncorrected refractive error with a growing burden worldwide. It is the principal complaint of most women during pregnancy. Although myopia has led to several consequences across the standard life of pregnant women, there is no previous study in Ethiopia regarding this topic. Thus, this study determined the prevalence of myopia and identifies its associated factors among pregnant women attending antenatal care units at governmental health institutions in Gondar City District, Northwest Ethiopia. Methods An institution-based cross-sectional study design was conducted from 08 February to 08 April 2021. From the selected health centres, study participants were recruited by systematic random sampling technique. A pre-tested, structured-interviewer-administered questionnaire consisting of socio-demographic variables, obstetric and clinical-related variables was used to collect the required data. Non-cycloplegic refraction was performed using trial lenses, trial frames, and retinoscopy in a semi-dark examination room. EpiData 3 and STATA 14 were used for data entry and statistical analysis respectively. Both bivariable and multivariable binary logistic regression analyses were executed to identify associated factors of myopia. Variables with a p-value ≤0.05 in the multivariable logistic regression analysis were declared as statistically significant with myopia. Model fitness was checked by Hosmer and Lemeshow goodness of test (at p > 0.05) Results A total of four-hundred and twenty-three pregnant women participated with a 100% response rate in this study. The overall prevalence of myopia among pregnant women was 26.48% (95% CI: 22.48–30.91). Eighty-Eight (20.81%) and Eighty-Four (19.85%) of the study participants had myopia in their right and left eyes respectively. The prevalence of myopia was significantly associated with age (AOR = 1.17; 95% CI: 1.09–1.28), the third trimester of gestation (AOR = 2.05, 95% CI: 1.08–3.90), multi & grand multipara (AOR = 3.15; 95% CI: 1.59–6.25), and history of contraceptive use (AOR = 3.30; 95% CI: 1. 50–7.28). Conclusion The finding of our study shows that there is a higher prevalence of myopia among pregnant women in our study area. Further prospective analytical studies regarding visual systems among pregnant women, particularly as a result of pregnancy, are strongly recommended.